The epidemiology of asthma and wheeze in primary school children in Mitchell's Plain, Cape Town, with special reference to the role of environmental tobacco smoke - Ehrlich, Rodney (Department of Public Health and Family Medicine, 2017)
This study was undertaken in the light of the increasing importance of childhood asthma worldwide, an apparently large burden of asthma morbidity disease in Cape Town, high local smoking rates and a lack of epidemiologic information on childhood asthma in South Africa. Two detailed literature reviews were undertaken. The first covered epidemiologic aspects of asthma and allergy in South Africa, as inferred from allergen and atopy studies, clinical series, and studies of prevalence and mortality. The second addressed the international literature on whether environmental tobacco smoke is associated with asthma, wheeze or bronchial hyperresponsiveness in general and asthmatic populations of children. This thesis is based on a self-administered questionnaire survey of the parents of 1 955 sub-8 pupils (90% response rate), aged 7 to 9 years, in Mitchell's Plain, a large, working class area of Cape Town Five empirical questions were asked: 1) is the prevalence of asthma and wheezing in primary school children? (2) What is the reliability (across two questionnaires) of questions about wheezing and asthma? 3) What are the household risk factors for wheezing and asthma; in particular, to what extent is household environmental tobacco smoke (ETS) a risk factor for asthma/wheeze? 4) Among children with asthma/wheeze, is there an association between ETS exposure and bronchial hyper-responsiveness (BHR), and 5) To what extent is asthma underrecognised and undertreated?